2020
DOI: 10.3920/jiff2019.0048
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities and food safety aspects of crickets (Acheta domesticus) reared under controlled conditions

Abstract: In an approach combining microbiological culture methods with high-throughput sequencing, this study investigated the microbial communities (bacteria, moulds and yeasts) in Swedish-produced edible crickets (Acheta domesticus) reared in a controlled environment. The effects of different feeds on microbial loads and populations in crickets were also studied. The crickets used were third-generation offspring from wild-caught individuals from Sweden, which are adapted to grow in a laboratory environment. The effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
3
19
1
2
Order By: Relevance
“…This might be explained by changes in the gut microbial community caused by reduced feed intake and also by stress, which might favour growth of certain bacteria (Martín-Peláez et al, 2009). The values found for TAC in the control group (no starvation) are comparable to those reported in the literature for fresh A. domesticus (Fernandez-Cassi et al, 2020;Grabowski and Klein, 2017b;Klunder et al, 2012;Vandeweyer et al, 2017). The only significant microbial reduction observed in the present study was in Enterobacteriaceae counts, which decreased with 24 h of starvation.…”
Section: Microbiological Analysessupporting
confidence: 83%
“…This might be explained by changes in the gut microbial community caused by reduced feed intake and also by stress, which might favour growth of certain bacteria (Martín-Peláez et al, 2009). The values found for TAC in the control group (no starvation) are comparable to those reported in the literature for fresh A. domesticus (Fernandez-Cassi et al, 2020;Grabowski and Klein, 2017b;Klunder et al, 2012;Vandeweyer et al, 2017). The only significant microbial reduction observed in the present study was in Enterobacteriaceae counts, which decreased with 24 h of starvation.…”
Section: Microbiological Analysessupporting
confidence: 83%
“…Several authors showed, in fact, that insects present attractive nutritional profiles, representing a potential source of essential amino acids and proteins of animal origin and other vitamins and minerals (Belluco et al, 2013(Belluco et al, , 2017Rumpold and Schlüter, 2013;Schlüter et al, 2017), so much so that consumers attentive to the decrease in meat consumption, believing that meat has a negative impact on human health (Mancini and Antonioli, 2019), seem to look for alternative protein sources (Belluco et al, 2013(Belluco et al, , 2017Menozzi et al, 2017;Fernandez-Cassi et al, 2020). In this context, novel foods such as cultured meat (Mancini and Antonioli, 2019) and insects (Fernandez-Cassi et al, 2020) are important.…”
Section: Vosviewer Discussionmentioning
confidence: 99%
“…are noted as the most hazardous species. Also in the most recent studies (Borremans et al, 2019;Fernandez-Cassi et al, 2020;Frigerio et al, 2020;Mancini et al, 2019b), (some of ) the same main biological safety hazards were addressed.…”
Section: Biological Risks Associated With Insects To Be Used In Food or In Both Food And Feedmentioning
confidence: 99%